Veterinary Nuclear Medicine: A Look into the Future (VETERINARIA, 2021)
The use of nuclear energy in veterinary medicine has been increasing over the last two decades. It mirrors the use in human health, but lags behind significantly. It is thought that animals are capable of undergoing almost any diagnostic or therapeutic procedure from human medicine. Strict rules about the use of nuclear energy in veterinary medicine are governed by the national authorities, and harmonized by the world leading authority in the field, the International Atomic Energy Agency (IAEA). Veterinary nuclear medicine has a clear methodology based on human medicine. Specificities relate to animals as patients, their lack of conscious cooperation, radiation safety measures in the light of animals’free movement, scarcety in trained staff and interest in referring at the side of veterinarians. Of primary concern remain the financial considerations, directly affecting the availability of veterinary nuclear services. Developed countries top the lists with services offered in veterinary nuclear medicine. Veterinary nuclear imaging can be preclinical for research purposes and clinical for diagnostic purposes. Isotopes of higher emission energies can be applied for therapeutic purposes to treat diseases. Such a combined use of isotopes for diagnostic and therapy gives a rise to the new field of theranostics. Nuclear images are created by injecting radioactive isotopes into animals, which then accumulate in the organs, depicting their morphology or function. Imaging is made by a scintillation gamma camera. Nuclear images are called nuclear scans, and the technique is called scintigraphy. Most commonly used radioactive isotope for diagnostic imaging is technetium Tc-99m, and for treatment iodine I-131. Scintigraphies most commonly performed on animals are thyroid, bone, liver and renal, all indicated in specific clinical scenarios. Number of both production and companion animals in the world is increasing. Consequently, demand for veterinary services has also been increasing, so that standard animal care needs constant improvement. That is why a need for more and novel diagnostic and therapeutic procedures, including the nuclear ones, will become more evident. Novel trends in veterinary nuclear medicine follow the trends in human medicine and are rapidly expanding. They include both research and clinical veterinary medicine.
Keywords: Imaging; isotopes; scintigraphy; veterinary nuclear medicine